Epidemiology and outcomes of carbapenem-resistant Klebsiella pneumoniae infections in patients with hematological malignancies from 2014 to 2022 - Meng Li; Liyan Ye; Zhenghao Yu; Hongwu Yao; Yunxi Liu; Guanglei Wang; Mingmei Du (Frontiers in Microbiology, 2025)
BackgroundWe aimed to describe the epidemiology, cross-transmission, interventions, and outcomes of carbapenem-resistant Klebsiella pneumoniae (CRKP) infections in the hematological malignancies (HM) department of a hospital in China.MethodsThis prospective study was divided into three stages from 2014 to 2022: Period 1 (from 1 January 2014 to 4 March 2021), Period 2 (from 5 March 2021 to 31 December 2021), and Period 3 (from 1 January 2022 to 31 December 2022), with different measures implemented at each stage to evaluate the rate of new infections. The risk factors, epidemiological characteristics, data from all patients with CRKP, NGS gene sequencing molecular epidemiology analysis, and cross-transmission were described.ResultsA total of 217 patients with K. pneumoniae isolates, including 38 (17.5%) patients with CRKP isolates, were confirmed in the HM department. The total rate of CRKP in KP isolates was 17.5%. The predominant clone in the HM department was ST11 CRKP producing the KPC-2 enzyme (21, 70.0%). A total of 23 cases of HM department-acquired CRKP infections were identified, and five hospital cross-transmission events were observed. Four instances of CRKP dissemination were primarily related to clone ST11. Only one outbreak occurred at the end of Period 1, involving four cases of CRKP healthcare-associated infections (HAIs). After the implementation of outbreak intervention bundles at the end of Period 2, no cross-transmission occurred. The rate of CRKP in KP isolates decreased to 12.9% (only four CRKP isolates) in Period 3, down from a peak of 46.7% in Period 2 (including 14 CRKP isolates). Only one new carrier (0.9%) was identified during the two cross-sectional active screenings of the rectal swab. The 28-day mortality rate was 38.7% (12/31) in CRKP-infected patients.ConclusionThe prevalence of CRKP in the HM department was relatively low in the studied hospital. We found that interventions, including single-room isolation, enhanced disinfection, and skin decolonization, played a pivotal role in controlling the spread of HM-acquired CRKP infections.